Determinants of Wealth Inequality and Mobility in General Equilibrium - Thomas Fischer (Lund University, School of Economics and Management, Department of Economics, 2019)
What determines inequality and mobility of wealth? This paper quantifies in closed form both the bottom and the top (Pareto) tail of the distribution for a rich continuous-time model. The distribution is especially shaped by bequest motives, demographics, and the asset portfolio composition under idiosyncratic wealth risk. Factors that increase inequality also reduce mobility. The model - enriched by a realistic income process and non-trivial portfolio constraints - is solved in general equilibrium and calibrated to match US evidence. A bequest tax is shown to reduce inequality and increase mobility. Several partial-equilibrium intuitions do not carry over into general equilibrium.
Keywords: C68; D31; E21; G11; H23; 330; wealth inequality; mobility of wealth; portfolio selection; fat tails; bequest tax